Analysis on the Teaching Competence Competitions and Relevant Recommendations to Promote Teachers’ Comprehensive Abilities in Higher Vocational Colleges - Wu, Yuguang (Pacific International Journal, 2025)
By systematically comparing the evaluation rubrics of the Hunan “Chuyi Cup” Vocational Teachers’ Competency Competition with those of the national “SFLEP Cup” Foreign Language Teaching Contest, this paper identifies divergent assessment foci employed to gauge the professional competencies of higher-vocational English teachers. The study explicates the intrinsic relationships and mediating mechanisms through which teaching competitions influence teacher capacity building, drawing on empirical evidence of both exemplary practices and recurrent deficiencies observed in contest performances. On this basis, the paper proposes targeted recommendations for enhancing instructional competence, thereby furnishing a validated pathway for the sustained professional growth of English teachers in the vocational sector.